Pelaksanaan Terapi Kesehatan Untuk Menjaga Kebugaran Fisik Lanjut Usia (LANSIA) Di Kelurahan Kapasa Makassar - Yusnayanti, Cici; Pannyiwi, Rahmat; Muchsin, Wachyudi; Syarief, Syarifah Wahyuni Al; Mahoklory, Serly Sani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Everyone's physical and mental health will be affected by aging, therefore it is very important to maintain healthy lifestyle habits as we age to improve the quality of life for seniors. Individual movement for exercise to a fitness center is highly recommended, and even carrying out activities independently outside the home is also highly recommended. Even though sports activities are very important to do as an effort to maintain the body's immunity so that it can prevent the body from being infected with viruses. The best thing to maintain and improve the immune system is to exercise regularly. The purpose of this PkM is to provide training and promotive and preventive efforts for problems that are analyzed by the situation carried out by the PkM Team, PKK women, community members in Kapasa Village, Makassar. The training participants, totaling 36 elderly people, are an important part of efforts to reduce the morbidity rate of the elderly. The hope is that the elderly will benefit from maintaining healthy bodies in old age, so that participants will be enthusiastic about taking part in the training. Data was obtained that many mothers in the community complained about a lack of understanding of physical fitness. So assistance is needed to maintain physical fitness with Health Therapy. Another problem is that it is difficult for them to maintain physical fitness because there is no assistance. As for the results, the PkM team had an idea to overcome the problem, namely discussing it by finding a solution by providing information and training about health and physical fitness accompanied by mentoring and practicing health therapy. After that, community members will demonstrate the results of the training. The results of Health Therapy Practices to maintain the physical fitness of PKK mothers, residents of the Kapasa Makassar Village community, will be evaluated.